Guia Editores - Brito... et al. , Ronnie Fagundes de (Revista Teste, 2022)
Guia do usuário do OJS 3/ Ronnie Fagundes de Brito et al. -- Brasília: Ibict, 2018. 144 p ISBN 978-85-7013-144-7 DOI: 10.21452/ 978-85-7013-144-7